1988
DOI: 10.1128/aem.54.11.2723-2727.1988
|View full text |Cite
|
Sign up to set email alerts
|

Acetate production from hydrogen and [13C]carbon dioxide by the microflora of human feces

Abstract: Fecal suspensions from humans were incubated with 13Co2 and H2. The suspensions were from subjects who harbored 108 and 1010 methanogens per g (dry weight) of feces, respectively, and from a subject who did not harbor methanogens. Quantitative nuclear magnetic resonance spectroscopy showed that acetate labeled in both the methyl and carboxyl groups was formed by suspensions from the subject without methanogens and the subject with the lower concentrations of methanogens. The amounts of labeled acetate formed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
2

Year Published

1990
1990
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(50 citation statements)
references
References 20 publications
(18 reference statements)
4
43
2
Order By: Relevance
“…Since acetate can be absorbed from the rodent cecum and oxidized for energy [8,9], these data taken together with those of Yang et al [8] on the contribution of cecal acetate to rat nutrition, suggest that H2/CO 2 acetogenesis in rat ceca could support up to 0.25% of the animal's maintenance energy requirement. Recently, Lajoie et al [10] confirmed the findings of Prins and Lankhorst by using rat fecal contents, but they also found that rats from their colony were moderately methanogenic. Fecal suspensions used about 1/2 the added H2 for methanogenesis, the rest was used for acetogenesis.…”
Section: Rodentsmentioning
confidence: 74%
See 3 more Smart Citations
“…Since acetate can be absorbed from the rodent cecum and oxidized for energy [8,9], these data taken together with those of Yang et al [8] on the contribution of cecal acetate to rat nutrition, suggest that H2/CO 2 acetogenesis in rat ceca could support up to 0.25% of the animal's maintenance energy requirement. Recently, Lajoie et al [10] confirmed the findings of Prins and Lankhorst by using rat fecal contents, but they also found that rats from their colony were moderately methanogenic. Fecal suspensions used about 1/2 the added H2 for methanogenesis, the rest was used for acetogenesis.…”
Section: Rodentsmentioning
confidence: 74%
“…Methane (0.03-3 liters per day) is produced in the large intestine of 1/3 to 1/2 of all adult humans as a result of H2/CO 2 methanogenesis [19]. Wolin and Miller [19] hypothesized that in 'nonmethanogenic' individuals CO 2 reduction to acetate occurs, and recent experiments have shown that the magnitude of H2/CO z acetogenesis in fecal suspensions varies inversely with the number of viable methanogens (and methanogenie activity) in feces ( [10]; Table 2). Although a total synthesis of [t3C]acetate from t3co2+ Ha occurred with some fecal suspensions, it will still be important to verify that the process occurs during fermentation of normal colonic substrates (e.g.…”
Section: Manmentioning
confidence: 99%
See 2 more Smart Citations
“…These data confirm that MB and SRB were involved in H 2 metabolism in each individual. Other possible mechanisms of H 2 disposal in the colon include diffusional losses in breath and flatus, or the existence of alternative bacteriological oxidative processes such as dissimilatory nitrate reduction [25] or acetogenesis [41]. Although energetically less favourable than SO 2reduction or methanogenesis [42], acetogenesis in the large bowel may be favoured by the low pH environment of the proximal colon.…”
Section: Discussionmentioning
confidence: 99%